A success/failure paradox: reflection on a university-community engagement in Australia. Issue 4 (4th July 2018) - Murphy, Daniel; McGrath, Dianne
ABSTRACT: There has been an increasing interest within the academic literature on the role played by Higher Education Institutions in the social and economic development of their communities. The Australia Government has recently released its National Science and Innovation Agenda (NISA) which is designed to incentivise university-community research partnerships. In this article, the identified lack of Australian university-community engagement will be problematised through the experience of academics who undertook such an engagement in a regional university setting. A completed research project is used as a lens through which institutional factors impacting on collaborative projects between universities and their communities are identified. The difficulties of university-community engagement are unpacked and problematised so that the various forces contributing to the shortage of university-community partnerships can be better identified and understood. The unitary manner in which university-community research is to be reported under NISA is highlighted as a key barrier to regional research partnerships.